PLURAL CONTINUITIES AND FEMININE VISUALITIES IN CONTEMPORARY INDIAN SCULPTURE: PRACTICES OF VANDANA SINGH AND SOJWAL SAMANT - Kant, Shree; Urala, Ganesh (ShodhKosh: Journal of Visual and Performing Arts, 2026)
In Indian contemporary art, the concepts of diversity, tradition, and global dialogue are clearly reflected through various geographical and cultural art centers. This research paper explores the diversity and richness of Indian art through selected sculptural works by contemporary Indian women sculptors Vandana Singh (Varanasi) and Sojwal Samant (Vadodara). Emerging from the cultural and spiritual traditions of Varanasi, Vandana Singh’s sculptural practice articulates Indian classical sensibilities, human experiences, and inner emotional consciousness. Formal balance, rhythm, and cultural memory in her works strengthen the continuity of Indian art. In contrast, Sojwal Samant’s practice, associated with the contemporary art environment of Vadodara, engages with experimentation, conceptual approaches, and global contemporary art discourse. In her sculptural works, modernity and international influences are clearly visible at the levels of material, structure, and concept. This paper analyzes that both artists’ practices reflect various and complementary aspects of contemporary Indian sculpture. Continuity arises from feminine perspectives, regional uniqueness, and material transition. In order to show that Indian contemporary art has historical roots and is involved in the global discourse on art, the paper situates women's sculptural practice within larger, international discussions. The study present new perspectives on the various manifestations of plural continuity as well as the viewpoint of women on modern Indian sculpture.